2017
DOI: 10.1017/jfm.2017.235
|View full text |Cite
|
Sign up to set email alerts
|

Faraday wave–droplet dynamics: discrete-time analysis

Abstract: A droplet may ‘walk’ across the surface of a vertically vibrating bath of the same fluid, due to the propulsive interaction with its wave field. This hydrodynamic pilot-wave system exhibits many dynamics previously believed to exist only in the quantum realm. Starting from first principles, we derive a discrete-time fluid model, whereby the bath–droplet interactions are modelled as instantaneous. By analysing the stability of the fixed points of the system, we explain the dynamics of a walking droplet and capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 38 publications
6
90
0
Order By: Relevance
“…We then apply the methodology introduced by Durey and Milewski [26] to elucidate the statistical structure emerging in the chaotic regime.…”
Section: Quantization Of Mean Radius and Angular Momentummentioning
confidence: 99%
See 4 more Smart Citations
“…We then apply the methodology introduced by Durey and Milewski [26] to elucidate the statistical structure emerging in the chaotic regime.…”
Section: Quantization Of Mean Radius and Angular Momentummentioning
confidence: 99%
“…Well-separated clusters formed for each chaotic trajectory, which motivated the application of K-means clustering [26]. The centroids of each cluster were then combined on a separate plot for varying spring constant k and showed an approximate double quantization in L z and R [26]. Their study raised the intriguing possibility that the double quantization reported by Perrard et al [13] is more pronounced in the chaotic than the periodic regime.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations